Determinants of historic and cultural landmark designation: why we preserve what we preserve - Douglas S. Noonan; Douglas J. Krupka (Institute for the Study of Labor (IZA), 2008)
There is much interest among cultural economists in assessing the effects of heritage preservation policies. There has been less interest in modeling the policy choices made in historic and cultural landmark preservation. This paper builds an economic model of a landmark designation that highlights the tensions between the interests of owners of cultural amenities and the interests of the neighboring community. We perform empirical tests by estimating a discrete choice model for landmark preservation using data from Chicago, combining the Chicago Historical Resources Survey of over 17,000 historic structures with property sales, Census, and other geographic data. The data allow us to explain why some properties were designated landmarks (or landmark districts) and others were not. The results identify the influence of property characteristics, local socio-economic factors, and measures of historic and cultural quality. The results emphasize the political economy of implementing preservation policies.
urn:nbn:de:101:1-20081126364
Keywords: Z1; 330; Heritage preservation policy; landmark designation; Kulturpolitik; Landschaftspflege; Public Choice; USA